Designing A Syllabus of Collaborative English Teaching for Physics Study Program - Junining, Esti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2015)
The recommended model of teaching English for students of non-English department is collaborative teaching which provides subject lecturer‘s involvement in the curriculum design. This paper reported the process of designing a syllabus of collaborative teaching for ESP teaching in Indonesian context. As a part of curriculum design, this ESP syllabus focuses on content area reading in the area of physics. Several text types commonly used in physics department and vocabulary building of academic word lists and the ones related to physics area study were elaborated as well. The paper concludes that the implementation of this program needs high commitment from the stakeholders in order to make the program successfully implemented.